Relationship of Some Internal Factors with Open Defecation (OD) Behavior in Dusun Kandangan Tarik District Sidoarjo - Giri, Gede Bagus Subha Jana; Purnama, Marini Ayu; Wiratma, I Putu Bhayu (Universitas Wijaya Kusuma Surabaya, 2017)
OD or open defecation is one of activity that influenced many aspects, it can pollute the source of drinking water, contaminate the crops , and the one that causes many diseases that are related to GI (Gastrointestinal) tract infectious diseases. Even though in Subdistrict of Tarik many household already had latrines, but not make the society become open defecation free, as in Kandangan hamlet which the percentage of OD is 35% at 2014 . The main purpose of this study is to evidently expose several internal factors that influence OD behavior in Kandangan Hamlet,village of Banjarwungu, subdistrict of Tarik,Sidoarjo regency. This analytic study used cross sectional approach, with chi square to test the hypothesis. The population consisted of 1003 people that come from Kandangan Hamlet, ,with sample size 91 people determined through simple random sampling method, focused between 15-65 years old. Variable of this research consists of age, gender, level of education, and economic status, those variable considered as the Independent variables and OD behavior as the dependent variable. The result of this study shows that age, level of education, and economic statu respectively influenced OD behavior in Kandangan Hamlet, (p<0,05). While gender and habit were not influence the behavior of OD(p>0,05). Suggestion for this problem can be made through improvingt of promotion program regarding OD issues emphasizing the importance of latrines, recruiting health cadres that can giving understanding about the importance of latriney, helding latrine community gathering and giving credit system for building latrines as hope for improving level of ODF in the society.